2013
DOI: 10.1093/mnras/stt118
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dust properties of the proto-planetary nebula IRAS 18276−1431

Abstract: We investigate the circumstellar dust properties of the oxygen-rich bipolar protoplanetary nebula IRAS 18276-1431 by means of two-dimensional radiative transfer simulations of the circumstellar dust shell. The model geometry is assumed to have a torus and an envelope which consists of a pair of bipolar lobes and a spherical AGB shell. The parameters of the dust and the dust shell are constrained by comparing the spectral energy distribution (SED) and near-infrared intensity and polarisation data with the model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Since the polarizations are high and do not change much in the H-and K S -bands, the fraction of small particles is expected to be higher than that of the interstellar population. In our separated paper (Murakawa et al 2012), we found a similar result in PPN I18276 and that a size distribution function with a steep power index provides a good estimate: 0.05 μm ≤ a and n (a) ∝ a −5.5 exp (−a/a c ), where a c is the cut-off size (Kim et al 1994). In I16342, a c = 5.0 μm fits the H and K S band polarizations.…”
Section: Dust Particlessupporting
confidence: 68%
“…Since the polarizations are high and do not change much in the H-and K S -bands, the fraction of small particles is expected to be higher than that of the interstellar population. In our separated paper (Murakawa et al 2012), we found a similar result in PPN I18276 and that a size distribution function with a steep power index provides a good estimate: 0.05 μm ≤ a and n (a) ∝ a −5.5 exp (−a/a c ), where a c is the cut-off size (Kim et al 1994). In I16342, a c = 5.0 μm fits the H and K S band polarizations.…”
Section: Dust Particlessupporting
confidence: 68%
“…Later imaging in the optical and (near-)IR confirmed this view (e.g. Sánchez Contreras et al 2007;Gledhill et al 2011;Lagadec et al 2011;Murakawa et al 2013). Observations of H 2 and CO emission in the near-IR suggest a bipolar outflow velocity of ∼ 95 km s −1 .…”
Section: Oh 177-20mentioning
confidence: 86%
“…No fast outflow is detected in the submillimetre CO emission. In Murakawa et al (2013), a model was created to match the near-IR spectral energy distribution and polarised emission. They conclude, assuming a distance of 3 kpc, that most of the dust resides in a torus with inner and outer radii of 30 and 1000 au.…”
Section: Oh 177-20mentioning
confidence: 99%
“…However hints of the hyperwind can already be seen in the models of IRAS 17150−3224 and other post-AGB sources (e.g. IRAS 16432−3814 in Dijkstra et al 2003or IRAS 18276−1431in Murakawa et al 2013. Meixner et al (2002) show that, at its highest, the mass-loss rate of IRAS 17150−3224 must have been of the order of 8.5 × 10 −3 M /yr.…”
Section: Introductionmentioning
confidence: 98%